Peran LLDIKTI Wilayah 2 dalam Proses Sosialisasi Aplikasi AMANDA Sebagai Media Absensi Dosen ASN di Universitas Bina Darma - Anie Yusti Wara; Isna Wijayani; Rahma Santi Zinaida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to describe the role of AMANDA socialization as a means of recording ASN Lecturer Attendance (AMANDA) for LLDIKTI Region 2 at Binadarma University. This study was conducted using a descriptive qualitative method design. The use of a descriptive qualitative research design in this study was intended to describe and analyze the process of socialization of the AMANDA ASN Lecturer Attendance (AMANDA) application in LLDIKTI Region II. Data in the form of information and statements related to the research focus were collected through observation, interviews, and documentation techniques. The collected data were then analyzed qualitatively by describing it in depth, guided by the established research objectives. The results show that the socialization of the AMANDA application has been quite effective through various media, such as face-to-face meetings, official circulars, and the use of online communication groups. This made it easier for ASN lecturers to understand the purpose and how to use the application, although in the initial stages there were still technical obstacles and limited understanding.